MENTORING AND COACHING APPROACHES IN TUTORING ACTIVITIES (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article highlights the significance of mentoring and coaching approaches in tutoring activities, as well as their differences and similarities. Mentoring is the process of transferring knowledge and skills by an experienced specialist, while coaching is a collaborative method aimed at unlocking and developing personal potential. In tutoring, these approaches support students in independent learning, self-awareness, and personal development. The article also emphasizes the tutor's role in enhancing the quality of education through communicative skills, an individual approach, and developmental conversations.